Predicting Ad Click-Through Rates in Digital Marketing with Support Vector Machines - Thosporn Sangsawang (Journal of Digital Market and Digital Currency, 2024)
This study investigates the effectiveness of Support Vector Machines (SVM) in predicting click-through rates (CTR) in digital marketing campaigns. Utilizing a dataset comprising user demographic and behavioral data, the research aims to develop a predictive model to forecast ad clicks accurately. The primary objectives include conducting exploratory data analysis (EDA), preprocessing data, training the SVM model, and evaluating its performance using standard metrics. The dataset includes features such as Daily Time Spent on Site, Age, Area Income, Daily Internet Usage, and Gender. Key findings from the EDA reveal that "Daily Time Spent on Site" and "Daily Internet Usage" are significant predictors of CTR, with notable correlations. The SVM model, trained on this data, demonstrated exceptional performance, achieving an accuracy of 97.65%, a precision of 98.58%, a recall of 96.53%, and an F1-score of 97.54%. These results confirm the model's robustness and reliability, indicating its potential for optimizing digital marketing strategies. The study's significance lies in its contribution to the fields of digital marketing and predictive analytics by showcasing the applicability and advantages of SVM in predicting user behavior. These insights can help marketers optimize ad placements, enhance user engagement, and improve return on investment. Practical implications include strategies for targeted and personalized marketing based on key user demographics and behaviors. Despite the promising results, the study acknowledges limitations such as the dataset size and scope of features. Future research should focus on utilizing larger and more diverse datasets, incorporating additional features, and exploring other advanced machine learning algorithms. This research encourages further exploration of machine learning applications in digital marketing to enhance predictive accuracy and campaign effectiveness. By addressing these aspects, this study aims to advance the academic understanding and practical implementation of predictive analytics in digital marketing, providing a robust framework for future applications.